Impact of utilitarian value and hedonic value on purchase in online store in Indonesia (Research, Society and Development, 2020)
Nowadays, Indonesia shopping patterns have significantly changed. E-commerce continues to grow rapidly as online shopping has become increasingly attractive. Online shopping saves time and offers convenience. This study was conducted in order to assess the impact of utilitarian and hedonic values on purchasing from online stores in Indonesia. The focus of the assessment was on five dimensions of hedonism and utilitarianism, which are: usefulness, enjoyment, ease of use, trustworthiness, and distribution channel (settlement). A total of 484 respondents were randomly asked to be participants. A questionnaire was the research instrument used to survey the participants for data gathering. The data was then analyzed using Structural Equation Modeling (SEM). Among the indicators tested, it was found that usefulness, enjoyment, ease of use, and distribution channel impacted hedonic values and utilitarian values significantly. Trustworthiness was the dimension that was not significant. For this study, the hypothesis was made that usefulness and enjoyment positively impacted impulsiveness. It can be concluded that whether due to utilitarian, hedonic, or impulsive motives, it will not be a problem. Indonesian shoppers will make purchases thru online shopping even if they have different motivations and purposes.